Building supply chain resilience amid Covid-19: Post-Pandemic strategies for hotel industry - Rini, Poppy Laksita; Fikri, Muhammad Ali (Asian Management and Business Review, 2022)
One of the businesses where its supply chain management is affected by the risks and major consequences due to Covid-19 is the hotel and tourism industry. As an industry based on human mobility and close social interaction, the tourism and hotel industry has the potential to not only become the center of the spread of the virus but also be the party that bears the most consequences for this pandemic condition. As one of the main tourism destinations in Indonesia, the hotel industry in Yogyakarta City is also struggling with this pandemic situation. One of the steps that can be taken in dealing with disruptive conditions is to create Supply Chain Resilience in the organization's business activities. By conducting the in-depth interview, this qualitative study aims to explore the strategies that have been taken by hotel industry in Yogyakarta City to build supply chain resilience for the post-pandemic condition. Various themes that emerged from the content analysis of interview responses related to the building supply chain resilience strategies amid Covid-19 pandemic have been consised and presented. Based on the content analysis that emerged out of the qualitative enquiry, this study found several strategies are suggested to build supply chain resilience. The strategies that have been successfully conducted in the hotel industry in order to make the business bounce back after the pandemic such as creating work flexibility as HR strategy, managing supply and demand uncertainty, creating disaster management operating procedure, and entering multi-business and multi-channel platforms.